A Functional Approach to Local Exhaustion of Remedies in International Law - Divesh Kaul (Washington University Global Studies Law Review, 2025)
Exhaustion of local remedies lies at the crossroads of customary international law, state sovereignty, and the individual rights protected under international law. Originally a customary international law doctrine with a foundation in diplomatic protection, the evolution of the local remedies rule has coincided with the progress of international law. Specialized branches of international law, whether human rights or investor-state arbitration, witness the principle’s use. From the perspectives of general international law, human rights law, and foreign investment protection, this paper argues: first, the local remedies rule advances an interaction between the national and international orders guided by law, and second, it essentially envisages a balance between states’ obligations and individuals’ international standing and their right to seek redressal under the aegis of international law principles.
Keywords: local remedies; customary international law; international law; state sovereignty; functional; local exhaustion; diplomatic protection; progress; human rights; investor-state; arbitration; general international law; human rights law; foreign investment; foreign investment protection; state obligations; international standing; redress; international law principles